Older Adults Exhibit a Nine-Fold Increased Risk of Type 2 Diabetes Mellitus: Evidence from a Hospital-Based Cross-Sectional Analysis - Ni Putu Widyanti Suastiari; Andiani (Indonesian Journal of Medicine, 2025)
Background: Type 2 diabetes mellitus represents a significant global health burden with increasing prevalence worldwide. Age and gender are recognized as important demographic risk factors influencing diabetes incidence. This study aimed to determine the relationship between age and gender with the incidence rate of type 2 diabetes mellitus at Bhayangkara Pusdik Brimob Watukosek Hospital. Subjects and Method: This cross-sectional study conducted at internal medicine polyclinic, Bhayangkara Pusdik Brimob Watukosek Hospital, Pasuruan, East Java, Indonesia, from October 2020 to May 2021. Study subjects of 250 patients were selected using total sampling technique. Secondary data from medical records were analyzed using odds ratio calculations to determine associations between age (categorized as high-risk ≥45 years vs low-risk <45 years) and gender with type 2 diabetes mellitus incidence. Data were analyzed using a multiple logistic regression. Results: Among 250 respondents, 140 (56.00%) were diagnosed with type 2 diabetes mellitus. High-risk age group comprised 136 respondents (54.40%), with 107 (76.40%) having diabetes. Female respondents totaled 148 (59.20%), with 80 (57.10%) having diabetes. Age demonstrated significant association with diabetes incidence (OR= 9.06; 95% CI= 5.15 to 15.93; p<0.001), indicating that high-risk age individuals were nine times more likely to develop diabetes compared to low-risk age individuals. Gender showed no significant association with diabetes incidence (OR= 0.82; 95% CI= 0.48 to 1.41; p=0.475). Conclusion: Age has a significant relationship with type 2 diabetes mellitus, while gender shows no significant association.